Effect of Pretreatment on Solar Dehydration of Selected Varieties of Onion - Edukondalu, L; Samuel, D.V.K (Journal of Agricultural Engineering, 2009)
The kinetics of solar drying of pre-treated onion slices (Pusa White Round, Pusa White Flat and Pusa Madhvi) of thickness 2 mm was studied at an air flow rate of 0.044m/s. Pre-treatments consisted immersion of slices in chemical solutions of sodium chloride, potassium metabisulphite and sodium benzoate at three different concentration levels (0.5%, 1.0% and 1.5%) of each chemical. The variety, chemical and chemical concentration level influenced the drying of onion flakes. Pre-treatment with sodium chloride gave the maximum value of drying constant as 1.256. Variety too influenced the drying of onion. The moisture loss was fast in Pusa White Round (PWR) compared to Pusa Madhvi (PM) and Pusa White Flat (PWF).